ANALYSIS OF FACTORS INFLUENCING STUDENTS’ SELF-LEADERSHIP: A PLS-SEM APPROACH IN THE MBKM PROGRAM AND INDUSTRIAL INTERNSHIPS - Tutik Susilowati; Yosep Tegar Prameswara (Universitas Labuhanbatu, 2026)
Purpose – This study aims to examine the factors influencing students’ self-leadership, particularly through participation in the Merdeka Belajar Kampus Merdeka (MBKM) program and an industrial internship. Therefore, this study seeks to address this gap by analyzing the role of MBKM and industrial internship experiences in enhancing students’ self-leadership.Methodology – This study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. Data were collected using a previously validated closed-ended questionnaire. The study population consisted of students at Sebelas Maret University enrolled in the MBKM program. The sampling technique employed was convenience sampling. A total of 115 respondents were recruited for the study.Findings – This study confirms several factors that appear to influence students’ self-leadership. A direct relationship confirms that both the MBKM program and industrial internship programs can enhance students’ self-leadership. Other findings indicate an indirect relationship whereby the MBKM program influences self-leadership through the industrial internship.Contribution – This study provides new insights into the factors that enhance students’ self-leadership. The findings indicate that the Merdeka Belajar Kampus Merdeka (MBKM) program, designed to provide real-world experience through direct workplace engagement, has proven effective in enhancing students’ self-leadership skills